Fixed frequency control with modified PSO-PIλDμ controller for power factor correction and fast regulation. (29th April 2022) - Babu, Jambulingam Jawahar; Thirumavalavan, Vinopraba
A new type of converters, namely, Luo converters, has become popular in the power electronics field in recent years. An AC-DC converter which needs power factor correction (PFC) at the fore side requires dc-dc topology between load and bridge rectifier. In the proposed work, positive output super lift elementary type Luo converter is used as a PFC topology between uncontrolled rectifier and load. Power quality indices will vary when an AC-DC converter exposed to load and line deviations. Fixed frequency control (two sensors only required) along with modified-particle swarm optimisation (PSO) tuned fractional order proportional integral derivative (FOPID) controller is proposed. This scheme enhances the power quality, as well as this combination makes an AC-DC converter settle fast for load and line transitions. MATLAB/Simulink environment is used to carry out extensive simulation.